Ministry across cultures : sharing the Christian faith in Asia - Beattie, Warren R. (Regnum studies in mission., 2016)
At a time when more and more Christians are coming across people from different cultural backgrounds this book addresses a number of important questions. How do we understand what culture is all about? How do we reach out to people from different cultures? What impact does culture have on "making disciples"? What impact does culture have on the local church? This book seeks to address and answer these questions - it is relevant to all Christians including those who are members or leaders of local churches who want to reach out to their neighbours and encourage them to be part of the church as